Amorphous Chalcogenide Semiconductors and Related Materials - Tanaka, Keiji; Shimakawa, Koichi (Springer New York : Imprint: Springer, 2011)
Amorphous Chalcogenide Semiconductors and Related Materials describes developments in the science and technology of this advancing class of materials. This book offers an up-to-date treatment of chalcogenide glasses, amorphous semiconductors, and photonics glasses from basic principles through to applications, while providing the reader with solid-state sciences for understanding the material property and technology. Chalcogenide glasses have a number of interesting and useful properties, which have been already exploited in the commercialization of new devices. The book describes them at length, while it also: Discusses technological applications such as nonlinear optical fibers, DVDs, and high resolution mammographic x-ray image detectors Includes coverage of noncrystalline semiconductors with glassy semiconductors Amorphous or glassy chalcogenides are a kind of noncrystalline and thermodynamically quasi-stable solids. Such materials possess totally different properties than crystalline solids, and therefore warrant detailed discussion and description, which Amorphous Chalcogenide Semiconductors and Related Materials provides.